A descriptive-contrastive analysis of the English passive clauses and the Ilongo-Hiligaynon goal focus clauses - Canieso, Norberto A. 1934- (s.n.], 1971)
This seminar paper is an attempt to analyse the English passive clauses in contrast with the goal focus clauses of Ilongo-Hiligaynon. The socio-cultural setting upon which both languages under study operate is taken as a backdrop of the analysis.